2023
DOI: 10.18196/jfaps.v3i2.15992
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Vitamin C Concentration Analysis of Gandaria (Bouae macrophylla Griff) Ethanol Extract Using Spectrophotometry UV Vis

Abstract: Antioxidants are chemical compounds that donate one or more electrons to free radicals to inhibit free radical reactions. One of the potential antioxidant sources is gandaria fruit (Bouea Macrophylla Griff). This research aims to determine the antioxidant activity and vitamin C content of the gandaria fruit extract. Gandaria fruit was macerated with ethanol as a solvent. Furthermore, the rotated extract was carried out for the phytochemical screening. The results of the phytochemical screening of the gandaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…18 In this study, the antioxidant activity test was carried out on 3 cream mask preparation formulas from the ethanol extract of jotang herbs in each formula, with the aim of knowing the IC 50 value in each formula for the preparation of jotang herb extract cream masks with extract ratios as much as 1 gram and 10 grams and to find out the comparison of mugwort cream masks. Measurement of the absorbance of cream mask samples was carried out with various concentrations (2,4,8,16, and 32 ppm) and then measured at a wavelength of 517 nm. The results of the IC50 value of the antioxidant test for cream mask preparations from the ethanol extract of the jotang herb (Acmella paniculata) showed that Formula 0 cream masks had very strong antioxidants (40.1959 µg/ml) and Formula I had very strong antioxidant value (25.663 µg/ml).…”
Section: Antioxidant Activity Test Of Jotang Herb (Acmella Paniculata...mentioning
confidence: 99%
See 1 more Smart Citation
“…18 In this study, the antioxidant activity test was carried out on 3 cream mask preparation formulas from the ethanol extract of jotang herbs in each formula, with the aim of knowing the IC 50 value in each formula for the preparation of jotang herb extract cream masks with extract ratios as much as 1 gram and 10 grams and to find out the comparison of mugwort cream masks. Measurement of the absorbance of cream mask samples was carried out with various concentrations (2,4,8,16, and 32 ppm) and then measured at a wavelength of 517 nm. The results of the IC50 value of the antioxidant test for cream mask preparations from the ethanol extract of the jotang herb (Acmella paniculata) showed that Formula 0 cream masks had very strong antioxidants (40.1959 µg/ml) and Formula I had very strong antioxidant value (25.663 µg/ml).…”
Section: Antioxidant Activity Test Of Jotang Herb (Acmella Paniculata...mentioning
confidence: 99%
“…Antioxidant compounds are needed for the body to protect against exposure to free radicals, which work by donating electrons to compounds that have oxidant properties so that they easily inhibit oxidant activity. 2 One of the plants that contain antioxidants and is often used is the jotang plant (Acmella paniculata), which has an IC50 value of 1.77 µg/ml. It is a herb that grows wild in gardens, along rice fields, river banks, and moist soils in tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%